Mice lacking glutamate carboxypeptidase II develop normally, but are less susceptible to traumatic brain injury. (28th April 2015) - Gao, Yang; Xu, Siyi; Cui, Zhenwen; Zhang, Mingkun; Lin, Yingying; Cai, Lei; Wang, Zhugang; Luo, Xingguang; Zheng, Yan; Wang, Yong; Luo, Qizhong; Jiang, Jiyao; et al.
Abstract Glutamate carboxypeptidase II (GCPII) is a transmembrane zinc metallopeptidase found mainly in the nervous system, prostate and small intestine. In the nervous system, glia‐bound GCPII mediates the hydrolysis of the neurotransmitter N‐acetylaspartylglutamate (NAAG) into glutamate and N‐acetylaspartate. Inhibition of GCPII has been shown to attenuate excitotoxicity associated with enhanced glutamate transmission under pathological conditions. However, different strains of mice lacking the GCPII gene are reported to exhibit striking phenotypic differences. In this study, a GCPII gene knockout (KO) strategy involved removing exons 3–5 of GCPII. This generated a new GCPII KO mice line with no overt differences in standard neurological behavior compared to their wild‐type (WT) littermates. However, GCPII KO mice were significantly less susceptible to moderate traumatic brain injury (TBI). GCPII gene KO significantly lessened neuronal degeneration and astrocyte damage in the CA2 and CA3 regions of the hippocampus 24 h after moderate TBI. In addition, GCPII gene KO reduced TBI‐induced deficits in long‐term spatial learning/memory tested in the Morris water maze and motor balance tested via beam walking. Knockout of the GCPII gene is not embryonic lethal and affords histopathological protection with improved long‐term behavioral outcomes after TBI, a result that further validates GCPII as a target for drug development consistent with results from studies using GCPII peptidase inhibitors. The peptide neurotransmitter N‐acetylaspartylglutamate (NAAG) suppresses glutamate transmission through selective activation of pre‐synaptic Group II metabotropic glutamate receptor subtype 3 (mGluR3) after traumatic brain injury (TBI). However, synaptically released NAAG is hydrolyzed to form N‐acetylaspartate and glutamate mainly by Glutamate carboxypeptidase II (GCPII), losing neuroprotective effect. In this study, we found that knock out of the GCPII gene is not embryonic lethal and affords histopathological protection with improved long‐term behavioral outcomes after TBI.